Distributional Impact of Tax, Welfare and Public Sector Pay Policies: 2009-2012 - CALLAN, TIM; KEANE, CLAIRE; WALSH, JOHN (ESRI, 2012)
The banking and fiscal crises, coupled with the worldwide Great Recession, have led to major declines in Ireland?s national income. In this article, we examine the direct impacts of changes in income?related taxes and social welfare policies on disposable incomes across the income distribution and for different family types. We also examine the effects of changes in public sector pay. The size and shape of the impacts in Budget 2012 are compared with the cumulative impact of policy over the full period since the initial budgetary response to the emerging crisis in October 2008. We also draw on recent work on the distributional impact of austerity packages in other EU countries to see how Ireland?s policy impacts compare with countries including Greece, Spain and the UK.
PUBLISHED
Dublin
Keywords: Income-related taxes; social welfare; policy; public sector pay; austerity